Exploring GPT-3 - Tingiris, Steve; Kinsella, Bret (Packt Publishing, 2021)
Get started with GPT-3 and the OpenAI API for natural language processing using JavaScript and Python Key Features Understand the power of potential GPT-3 language models and the risks involved Explore core GPT-3 use cases such as text generation, classification, and semantic search using engaging examples Plan and prepare a GPT-3 application for the OpenAI review process required for publishing a live application Book Description Generative Pre-trained Transformer 3 (GPT-3) is a highly advanced language model from OpenAI that can generate written text that is virtually indistinguishable from text written by humans. Whether you have a technical or non-technical background, this book will help you understand and start working with GPT-3 and the OpenAI API. If you want to get hands-on with leveraging artificial intelligence for natural language processing (NLP) tasks, this easy-to-follow book will help you get started. Beginning with a high-level introduction to NLP and GPT-3, the book takes you through practical examples that show how to leverage the OpenAI API and GPT-3 for text generation, classification, and semantic search. You'll explore the capabilities of the OpenAI API and GPT-3 and find out which NLP use cases GPT-3 is best suited for. You'll also learn how to use the API and optimize requests for the best possible results. With examples focusing on the OpenAI Playground and easy-to-follow JavaScript and Python code samples, the book illustrates the possible applications of GPT-3 in production. By the end of this book, you'll understand the best use cases for GPT-3 and how to integrate the OpenAI API in your applications for a wide array of NLP tasks. What you will learn Understand what GPT-3 is and how it can be used for various NLP tasks Get a high-level introduction to GPT-3 and the OpenAI API Implement JavaScript and Python code examples that call the OpenAI API Structure GPT-3 prompts and options to get the best possible results Select the right GPT-3 engine or model to optimize for speed and cost-efficiency Find out which use cases would not be suitable for GPT-3 Create a GPT-3-powered knowledge base application that follows OpenAI guidelines Who this book is for Exploring GPT-3 is for anyone interested in natural language processing or learning GPT-3 with or without a technical background. Developers, product managers, entrepreneurs, and hobbyists looking to get to grips with NLP, AI, and GPT-3 will find this book useful. Basic ...